2016
DOI: 10.31073/agrovisnyk201609-04
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of chlorophyll pigment in leaves of soft winter wheat annual at different stages of organogenesis

Abstract: The purpose. Study of physiological state of soft winter wheat at different stages of organogenesis by determination of amount and activity of chlorophyll pigment in probed plants and response of these cultivars to conditions of overwintering. Methods. The method is used of photoinduction of fluorescence of chlorophyll pigment which enables in field conditions to determine amount of chlorophyll pigment and photosynthetic rate of 7 cultivars of soft winter wheat. Results. The essential variance in amount and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…We have shown that with the caterpillar development (during all 5 of its generations), a gradual decrease in the values of all the main indicators (F о , F m , F p and F St ) is observed, which affects the general physiological state of the leaf on which the C. ohridella mine is located. To characterize the photosynthetic apparatus under stress at the leaf level during the quick stage, the ratio of variable fluorescence F v to the maximum F m level is often used, which is considered an indicator of potential photosynthetic activity in the leaf (Starychenko et al, 2016;Tseng & Chu, 2017;Scognamiglio et al, 2019). Fluorescence variability (F v ) is calculated as the difference between F m and F o values and it is a physiological indicator that reflects the influence of environmental and experimental factors on the plant (Alonso et al, 2017;Chitband et al, 2017;Huliaieva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that with the caterpillar development (during all 5 of its generations), a gradual decrease in the values of all the main indicators (F о , F m , F p and F St ) is observed, which affects the general physiological state of the leaf on which the C. ohridella mine is located. To characterize the photosynthetic apparatus under stress at the leaf level during the quick stage, the ratio of variable fluorescence F v to the maximum F m level is often used, which is considered an indicator of potential photosynthetic activity in the leaf (Starychenko et al, 2016;Tseng & Chu, 2017;Scognamiglio et al, 2019). Fluorescence variability (F v ) is calculated as the difference between F m and F o values and it is a physiological indicator that reflects the influence of environmental and experimental factors on the plant (Alonso et al, 2017;Chitband et al, 2017;Huliaieva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ecol. Noospher., 31(1) 13 Для характеристики фотосинтетичного апарату в умовах стресу на рівні листка на етапі швидкої фази частіше використовують співвідношення варіабельної флуоресценції F v до максимального рівня F m , яке вважається показником потенційної фотосинтетичної активності листка (Starychenko et al, 2016;Tseng, Chu, 2017). Варіабельність флуоресценції (F v ) розраховується як різниця показників F m та F o і є фізіологічним показником, який відображає дію екологічних та експериментальних чинників на рослину (Huliaieva et al, 2018).…”
Section: результати та їх обговоренняunclassified
“…The analysis of scientific literature showed that the study of the characteristics of the photosynthetic apparatus of wild and agricultural plants has been carried out by many scientists. Oleksiychenko et al (2013), Vasylenko (2015), Starychenko (2016), Shepeliuk et al (2017), Mamonova et al (2018) studied the functional state of the pigment complex of the leaf apparatus of woody plants using the method of induction of chlorophyll fluorescence. Zelenyanska (2009) investigated the induction of chlorophyll fluorescence in the leaves of grape seedlings to determine their resistance to high air temperatures.…”
Section: Introductionmentioning
confidence: 99%